Government Expenditure and Poverty Reduction in Nigeria, 1986-2022: A Disaggregated Approach - Ejemezu, Charles; Ajala, Rosemary Bukola (African Journal of Stability and Development (AJSD), 2023)
Poverty in Nigeria is a complex issue that demands urgent government attention. With approximately 63% of the population living below the poverty line in 2022, understanding the relationship between government expenditure and poverty is crucial. Despite existing studies focusing on the impact of government expenditure on economic growth, few have explored the relationship between government expenditure from different sectors and poverty. This study aims to address this gap by investigating the effects of government expenditure in various economic sectors on poverty in Nigeria from 1986 to 2022. Using government expenditure on education, health, security, building and construction, and roads as proxies, and the head count index as a proxy for poverty, this study analyzed secondary data from the CBN Statistical Bulletin and National Bureau of Statistics. The Johansen cointegration and vector error correction mechanisms were employed as estimation methods. The findings indicate that all selected government expenditures had positive short-term effects on poverty, but negative long-term effects, except for government expenditures on roads. This suggests that government expenditure has a reducing effect on poverty in the long term, but is not effectively addressing poverty in the short term. The study concludes that government expenditure plays a significant role in reducing poverty in the long run. As a recommendation, the study suggests prioritizing infrastructure development, particularly in road construction and public transportation, to improve citizens' mobility, reduce transportation costs, and facilitate easy movement with the motive of reducing the poverty rate among Nigerians.